Biometric cryptosystems: A new biometric key binding and its implementation for fingerprint minutiae-based representation. (August 2016) - Jin, Zhe; Teoh, Andrew Beng Jin; Goi, Bok-Min; Tay, Yong-Haur
Abstract: Despite fuzzy commitment (FC) is a theoretically sound biometric-key binding scheme, it relies on error correction code (ECC) completely to mitigate biometric intra-user variations. Accordingly, FC suffers from the security–performance tradeoff. That is, the larger key size/higher security always trades with poor key release success rate and vice versa. Additionally, the FC is highly susceptible to a number of security and privacy attacks. Furthermore, the best achievable accuracy performance of FC is constrained by the simple distance metrics such as Hamming distance to measure the dissimilarity of binary biometric features. This implies many efficient matching algorithms are to be abandoned. In this paper, we propose an ECC-free key binding scheme along with cancellable transforms for minutiae-based fingerprint biometrics. Apart from that, the minutiae information is favorably protected by a strong non-invertible cancellable transform, which is crucial to prevent a number of security and privacy attacks. The scheme is not limited to binary biometrics as demanded in FC but instead can be applied to various types of biometric features and hence a more effective matcher can be chosen. Experiments conducted on FVC2002 and FVC2004 show that the accuracy performance is comparable to state-of-the-arts. We further demonstrate that the proposed scheme is robust against several major security and privacy attacks. Highlights: A new ECC-free biometric key binding scheme and the realization in fingerprint biometrics are proposed. A modified randomized GHE in constructing the cancellable transform is proposed. We performed several security and privacy analysis for the proposed scheme, like privacy attacks ARM and SKI. The proposed scheme can be applied to variety of biometric feature representations, not only binary string and matcher.